2019
DOI: 10.2967/jnumed.119.234559
|View full text |Cite
|
Sign up to set email alerts
|

Patients Resistant Against PSMA-Targeting α-Radiation Therapy Often Harbor Mutations in DNA Damage-Repair–Associated Genes

Abstract: Prostate-specific membrane antigen (PSMA) targeting alpha-radiation therapy (TAT) is an emerging treatment modality for metastatic castration-resistant prostate cancer. There is a subgroup of patients with poor response despite sufficient expression of PSMA in their tumors. The aim of this work was to characterize PSMA-TAT nonresponding lesions by targeted next-generation sequencing (tNGS). Methods: Out of 60 patients treated with 225 Ac-PSMA-617, we identified 10 patients that presented with a poor response d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 39 publications
1
56
1
Order By: Relevance
“…However, with the growing numbers of patients treated with TAT, the occurrence of non-responders or individuals who will relapse shortly after the treatment can be observed ( Figure 6). Targeted next-generation sequencing (tNGS) in responding vs. non-or only poor responding patients despite PSMA positivity to [ 225 Ac]Ac-PSMA-617 therapy revealed that DNA damage-repair and checkpoint genes are frequently mutated in poor and non-responders [111]. The mechanisms as to how the inherent or acquired resistances and gene mutations develop are far from being understood, and no strategies for risk stratification of patients exist yet.…”
Section: Atomic Nanogenerators In Modern Cancer Managementmentioning
confidence: 99%
“…However, with the growing numbers of patients treated with TAT, the occurrence of non-responders or individuals who will relapse shortly after the treatment can be observed ( Figure 6). Targeted next-generation sequencing (tNGS) in responding vs. non-or only poor responding patients despite PSMA positivity to [ 225 Ac]Ac-PSMA-617 therapy revealed that DNA damage-repair and checkpoint genes are frequently mutated in poor and non-responders [111]. The mechanisms as to how the inherent or acquired resistances and gene mutations develop are far from being understood, and no strategies for risk stratification of patients exist yet.…”
Section: Atomic Nanogenerators In Modern Cancer Managementmentioning
confidence: 99%
“…Resistance to therapy, which develops to some cancer drugs, is unlikely to occur to α-particle-emitting radionuclides, 26 although a high prevalence of mutations in the DNA damage response (DDR) genes was reported in a small group of patients who had not responded to 225 Ac-prostate-specific membrane antigen (PSMA)-617 treatment. 27 Moreover, the high energy of α particles, delivered within a small area in the tumor, damage cancer cells independently of local oxygen levels, thus overcoming hypoxia-induced resistance to therapy. 26 , 28 Notably, due to their short path length, potent radiation, and normal tissue sparing, TTCs may be a particularly attractive therapeutic choice for controlling the growth of micrometastatic cancer deposits in patients with disseminated cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Around 20% of patients treated with 225 Ac-PSMA-617 have a poor response (Table 5) or early resistance against 225 Ac-PSMA-617 [107], despite sufficient expression of PSMA and uptake of 225 Ac-PSMA-617 in their tumors [192]. Several combination treatments with PSMA-TAT have been proposed [173,192,193]. Their goal is to increase PSMA-TAT efficacy by using therapies with different action mechanisms together with TAT, keeping toxic effects to a minimum.…”
Section: Combination Treatments With Psma-tatmentioning
confidence: 99%
“…A single course of tandem therapy with low-activity 225 Ac-PSMA-617 and full-activity 177 Lu-PSMA-617 has enhanced response to PSMA-RLT and minimized xerostomia severity in men with late-stage/end-stage mCRPC [173,194]. There is a subgroup of patients (∼17%) with poor response to 225 Ac-PSMA-617 who harbor mutations in DNA damage-repair and checkpoint genes [192]. Combining PSMA-TAT and DNA damage-repair-targeting agents, such as poly(ADP-ribose)-polymerase inhibitors, have been suggested for these patients [192].…”
Section: Combination Treatments With Psma-tatmentioning
confidence: 99%
See 1 more Smart Citation